2004
DOI: 10.1111/j.1365-3156.2004.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Dengue vector prevalence and virus infection in a rural area in south India

Abstract: SummaryWe conducted a 2-year (1997)(1998)(1999) longitudinal, entomological and virological study in three dengue endemic villages in Vellore district, Tamil Nadu, to understand the dynamics of dengue transmission. Aedes aegypti (Linn.), Ae. albopictus (Skuse) and Ae. vittatus (Bigot) were the prevalent vector species. Aedes aegypti was breeding throughout the year with a Breteau index ranging from 9.05 to 45.49. Aedes albopictus and Ae. vittatus were prevalent mainly in the rainy season. Small water holding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 22 publications
3
47
0
6
Order By: Relevance
“…De nos jours, en Asie, Ae. albopictus est l'espèce la plus communément rencontrée dans des aires suburbaines et rurales (Tewari et al, 2004), mais aussi dans les villes où persiste une végé-tation arbustive comme à Kuala Lumpur, Singapour ou Tokyo. Ce rapprochement de l'homme lui a permis de coloniser de nouveaux territoires au gré des déplace-ments humains et de l'intensification des échanges commerciaux.…”
Section: Les Vecteursunclassified
“…De nos jours, en Asie, Ae. albopictus est l'espèce la plus communément rencontrée dans des aires suburbaines et rurales (Tewari et al, 2004), mais aussi dans les villes où persiste une végé-tation arbustive comme à Kuala Lumpur, Singapour ou Tokyo. Ce rapprochement de l'homme lui a permis de coloniser de nouveaux territoires au gré des déplace-ments humains et de l'intensification des échanges commerciaux.…”
Section: Les Vecteursunclassified
“…5,[8][9][10] Furthermore, dengue virus (DENV)-infected Ae. aegypti females were reported in the home environment in Southeast Asia [11][12][13][14][15][16][17][18][19][20] and the Americas. 7,[21][22][23][24][25][26][27] For example, we recently showed that DENV-infected Ae.…”
Section: Introductionmentioning
confidence: 99%
“…However, in both Sri Lanka, and India this pattern appears to have changed with the disease now spreading to rural areas as well 25 . Although vector densities are generally much higher in urban areas when compared to rural areas, vector densities in rural areas are now seen to be quite high 10,26 . Therefore, the potential 'threat' of major dengue outbreaks in rural areas is present.…”
Section: Future Trendsmentioning
confidence: 99%